Improving Decision-making for Sustainable Urban Transport: An Introduction to The DISTILLATE Research Programme - May, Anthony (European Journal of Transport and Infrastructure Research, 2009)
The policy measures needed to achieve more sustainable urban transport systems are now well understood. However, there remain serious barriers to the development and delivery of effective strategies. These include split responsibilities, lack of clarity in the policy process, inappropriate financing rules, lack of data and skills, limited public support and lack of political resolve. The series of papers in this special issue describe the research undertaken in an integrated research programme, DISTILLATE, which has developed a set of decision-support tools designed to help overcome these barriers. This paper outlines the context of the programme, which was conducted with sixteen local authority partners involved in the UK Local Transport Plan process. It describes the research approach, which focused on the barriers which were of the greatest importance to practitioners and the most researchable, and which used case studies, and action research, to understand problems and test solutions. It outlines the more detailed analysis of the barriers faced by local authorities. This demonstrated that the policy measures which were the most important were the most difficult to implement, and that the problems in doing so arose in all six technical areas of the research programme: monitoring, option generation, finance, prediction, appraisal and coordination. It also emphasised the need to distinguish between strategy development and scheme design. The paper describes the approach adopted to developing and testing the programme’s 19 products for strategy development and scheme design, and the overarching decision-support tool developed to aid their dissemination. It concludes with an assessment of the growing challenges in urban transport policy and of the need to improve the take-up of decision-support tools.